2020
DOI: 10.1155/2020/5172765
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Simplicillium sp. Ethyl Acetate Extract against High Glucose‐Induced Oxidative Stress in HUVECs

Abstract: This study aimed at investigating the cytoprotective effect of an ethyl acetate extract of insect fungi against high glucose- (HG-) induced oxidative damage in human umbilical vein endothelial cells (HUVECs). An insect fungus strain termed CH180672 (CH) was found for protecting HUVECs from HG-induced damage. In this study, CH was identified as Simplicillium sp. based on a phylogenetic analysis of ITS‐rDNA sequences. Ethyl acetate extract (EtOAc) of this strain (CH) was subjected to the following experiments. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Fill et al (2010) discovered an effective antioxidant compound, namely, phenylpropanoid amide, isolated from the endophytic fungus Penicillium brasilianum . Similarly, Tian et al (2020) found that Simplicillium sp. ethyl acetate extracts have excellent antioxidant activity, which contains various chemical components.…”
Section: Discussionmentioning
confidence: 88%
“…Fill et al (2010) discovered an effective antioxidant compound, namely, phenylpropanoid amide, isolated from the endophytic fungus Penicillium brasilianum . Similarly, Tian et al (2020) found that Simplicillium sp. ethyl acetate extracts have excellent antioxidant activity, which contains various chemical components.…”
Section: Discussionmentioning
confidence: 88%
“…A study showed that the ethyl acetate extract of an insect fungus Simplicillium sp. CH180672 protects the human umbilical vein endothelial cells from high glucose induced damage 21 . It is also observed that this action may be related to the regulation of the Nrf2/HO‐1 pathway.…”
Section: Secondary Metabolites Produced By Simplicillium and Emericel...mentioning
confidence: 92%
“…CH180672 protects the human umbilical vein endothelial cells from high glucose induced damage. 21 It is also observed that this action may be related to the regulation of the Nrf2/HO-1 pathway. As this species deeply indorsed the translocation of Nrf2 and its trans regulation on HO-1 and eventually reserved the severe level of reactive oxygen species and malondialdehyde induced by high glucose.…”
Section: Miscellaneousmentioning
confidence: 99%
“…The optimal concentrations of TXD and LPS were determined using a cell viability assay. The CMECs were then treated with 5 μ M of ML385 (Nrf2 inhibitor) to determine whether TXD inhibits inflammation by activating Nrf2 [ 22 ], after which they were seeded into 6-well plates at a density of 1 × 10 5 /well. The cells reached 80% confluency following overnight incubation.…”
Section: Methodsmentioning
confidence: 99%